1993
DOI: 10.1111/j.1365-2958.1993.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces antibioticus contains at least three oleandomycin‐resistance determinants, one of which shows similarity with proteins of the ABC‐transporter superfamily

Abstract: Three different DNA fragments of an oleandomycin producer, Streptomyces antibioticus, conferring oleandomycin resistance were cloned in plasmid pIJ702 and expressed in Streptomyces lividans and in Streptomyces albus. These oleandomycin resistance determinants were designated as oleA (pOR400), oleB (pOR501) and oleC (pOR800). oleA and oleC are closely linked in the chromosome as they were both obtained together in two cosmid clones that were isolated from a genomic library. Sequencing of the oleC resistance det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…These two components are biochemically coupled and are thought to form an efflux pump (236,237). Several homologues of DrrAB have been described for different species of drug-producing Streptomyces, conferring resistance to oleandomycin, tetronasin, mithramycin, and kasugamycin (151,220,279,404). Despite the general assumption that proteins in the Dra family confer resistance to specific drugs, there is some suggestion that they are also able to function as MDR determinants.…”
Section: Class 3 Abc Systems That Are Probably Not Importersmentioning
confidence: 99%
“…These two components are biochemically coupled and are thought to form an efflux pump (236,237). Several homologues of DrrAB have been described for different species of drug-producing Streptomyces, conferring resistance to oleandomycin, tetronasin, mithramycin, and kasugamycin (151,220,279,404). Despite the general assumption that proteins in the Dra family confer resistance to specific drugs, there is some suggestion that they are also able to function as MDR determinants.…”
Section: Class 3 Abc Systems That Are Probably Not Importersmentioning
confidence: 99%
“…Most bacterial ABC drug transporters mediate the export of specific antibiotics (17,55,76,130,183,197,210,212). The first true bacterial ABC multidrug transporter was found in Lactococcus lactis (20).…”
Section: Atp-dependent Multidrug Transportersmentioning
confidence: 99%
“…Several previously identified ABC transporters of Streptomyces spp. maintain self-resistance to, or accomplish the secretion of, antibiotics produced by those species (Linton et al 1994;Barrasa et al 1995;Olano et al 1995;Fernandez et al 1996;Ikeno et al 2000), and can be found outside the biosynthetic cluster encoding the antibiotic (Rodriguez et al 1993;Aguirrezabalaga et al 2000). Whether ecaA has a role in Act resistance or the secretion of actinorhodin has not been determined.…”
Section: Microarray Analysis Of Streptomyces Transcription Genes and Dementioning
confidence: 99%